Higiene Sanitasi dan Kejadian Infeksi Kecacingan pada Siswa Sekolah Dasar - Sondang Sidabutar (FORIKES, 2020)
Background: Higiene sanitation is a factor that is closely related to Helminthiases infection. Purpose: this study was to determine how the occurrence of sanitary hygiene with helminthiases infection in the District elementary school students 0913152014 in District Raya Simalungun. Method: The type of research was descriptive analytic with cross sectional approach. The population in this study were students of class I to class VI (91 people). The sampling technique was simple random sampling (48). The instrument used in this study was a laboratory test and a questionnaire. The data obtained in this study were analyzed using Chi-square test. Result: Based on Chi-square analysis of the relationship between hygiene and sanitation with the incidence of intestinal worms found handwashing (X2 = 23), the habit of cutting the nails (X2 = 8.21), the habit of eating raw foods (X2 = 12.24), latrine ownership (X2 = 11:47), type of flooring (X2 = 6.13), and the availability of clean water (X2 = 0.0276). Conclusion: From the results of research and discussion, it could be concluded that there was a correlation with the incidence of worm infection habit of hand washing, nail cutting habit, the habit of eating raw foods, floor of the house and latrine ownership. Keywords: sanitation; hygiene; helminthiases; elementary students ABSTRAK Latarbelakang: Higiene sanitasi merupakan faktor yang sangat erat dengan infeksi kecacingan.Tujuan: Tujuan penelitian adalah mengetahui bagaimana higiene sanitasi dengan kejadian infeksi kecacingan pada siswa Sekolah Dasar 091315 Kecamatan Raya Kabupaten Simalungun. Metode: Jenis penelitian ini adalah dekriptif analitik dengan pendekatan cross sectional. Populasi adalah siswa kelas I sampai kelas VI (91 orang). Teknik pengambilan sampel adalah simple random sampling (48). Instrumen yang digunakan adalah uji laboratorium dan kuesioner. Data yang diperoleh, dianalisis menggunakan rumus statistik uji Chi-square dengan t hitung (α = 0,05). Hasil: Berdasarkan analisis Chi-square hubungan antara higiene sanitasi dengan kejadian penyakit cacingan didapatkan kebiasaan mencuci tangan ( X2=23), kebiasaan memotong kuku (X2=8,21), kebiasaan mengkonsumsi makanan mentah (X2=12,24), kepemilikan jamban (X2=11.47), jenis lantai (X2=6.13), dan ketersediaan air bersih (X2=0.0276). Kesimpulan: ada hubungan kejadian infeksi kecacingan dengan kebiasaan mencuci tangan, kebiasaan memotong kuku, kebiasaan mengkonsumsi makanan mentah, lantai rumah dan kepemilikan jamban. Kata kunci: higiene; sanitasi; kecacingan; siswa SD